2020
DOI: 10.18268/bsgm2020v72n3a201219
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of Platinum-Group Elements (PGE) in Cerro Matoso and Planeta Rica Ni-Laterite deposits, Northern Colombia

Abstract: Platinum-group elements (PGE) are included among the so-called critical metals, and are essential metals for the technological industry. However, there are very few deposits in the world from which these metals can be extracted. The present work investigates three Ni-laterite profiles (hydrous Mg silicate type) formed over the ultramafic rocks of Cerro Matoso and Planeta Rica in Colombia. The main goal is to determine their PGE concentration and distribution, as well as to identify the carrier phases of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Previous studies on the mobility of PGE during lateritization processes revealed that acidic conditions (pH < 6 and Eh > 0.4) could lead to the dissolution of PGE‐bearing minerals, especially PPGE phases, and then they would undergo subsequent transportation in solution and accumulation in the oxidized Fe‐rich laterite profiles (Plimer & Williams, 1988; Talovina & Lazarenkov, 2001). The PGE are accumulated as PGE‐rich alloys, which co‐precipitate with Fe and Mn oxides under such acidic conditions (Bowles, Gize, & Cowden, 1994; Bowles, Gize, Vaughan, & Norris, 1994; Ndjigui & Bilong, 2010; Salpéteur et al., 1995; Tobόn et al., 2020). Complex Pt‐Ir‐Fe‐Ni alloys were recently found as inclusions and packed nanoparticles within pore spaces of Fe oxides and oxyhydroxides of the Loma Peguera Ni‐laterite deposit in the Dominican Republic (Aiglsperger et al., 2015, 2017) and in the Planeta Rica Ni‐laterite profiles of Northern Colombia (Tobόn et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on the mobility of PGE during lateritization processes revealed that acidic conditions (pH < 6 and Eh > 0.4) could lead to the dissolution of PGE‐bearing minerals, especially PPGE phases, and then they would undergo subsequent transportation in solution and accumulation in the oxidized Fe‐rich laterite profiles (Plimer & Williams, 1988; Talovina & Lazarenkov, 2001). The PGE are accumulated as PGE‐rich alloys, which co‐precipitate with Fe and Mn oxides under such acidic conditions (Bowles, Gize, & Cowden, 1994; Bowles, Gize, Vaughan, & Norris, 1994; Ndjigui & Bilong, 2010; Salpéteur et al., 1995; Tobόn et al., 2020). Complex Pt‐Ir‐Fe‐Ni alloys were recently found as inclusions and packed nanoparticles within pore spaces of Fe oxides and oxyhydroxides of the Loma Peguera Ni‐laterite deposit in the Dominican Republic (Aiglsperger et al., 2015, 2017) and in the Planeta Rica Ni‐laterite profiles of Northern Colombia (Tobόn et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The PGE are accumulated as PGE‐rich alloys, which co‐precipitate with Fe and Mn oxides under such acidic conditions (Bowles, Gize, & Cowden, 1994; Bowles, Gize, Vaughan, & Norris, 1994; Ndjigui & Bilong, 2010; Salpéteur et al., 1995; Tobόn et al., 2020). Complex Pt‐Ir‐Fe‐Ni alloys were recently found as inclusions and packed nanoparticles within pore spaces of Fe oxides and oxyhydroxides of the Loma Peguera Ni‐laterite deposit in the Dominican Republic (Aiglsperger et al., 2015, 2017) and in the Planeta Rica Ni‐laterite profiles of Northern Colombia (Tobόn et al., 2020). These observations are in good agreement with the previous studies, which indicated that the high contents of Pt, Pd, and Ru, as well as the transition metals such as Ni, Co, Cu, and Zn, in laterite profiles, are essentially hosted by secondary minerals like Fe‐oxy‐hydroxides or smectite clay minerals (Ndjigui & Bilong, 2010; Oberthür & Melcher, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The laterite profile at Yubdo is similar to other tropical lateritic occurrences, but it has been well exposed by the mining activity. The pit of the Ni mine at Cerro Matoso, Colombia, is also the result of mining activity (Tobón et al, 2020), and it shows a comparable profile with a cover of allochthonous soil over in situ red laterite with saprolite beneath (Fig. 8a,b).…”
Section: The Eluvial Regimementioning
confidence: 99%
“…PGM occurrences northern Colombia (after Tobón et al , 2020); (a) laterite overlying saprolite at the Cerro Matoso pit; (b) the laterite profile; (c) PGE in a drill hole at Planeta Rica; (d) PGM near the saprolite–laterite boundary from the same drill core.…”
Section: The Eluvial Regimementioning
confidence: 99%